Precision of a FDTD method to simulate cold magnetized plasmas - Pavlenko, I.V.; Melnyk, D.A.; Prokaieva, A.O.; Girka, I.O. (Вопросы атомной науки и техники, 2014)
The finite difference time domain (FDTD) method is applied to describe the propagation of the transverse electromagnetic waves through the magnetized plasmas. The numerical dispersion relation is obtained in a cold plasma approximation. The accuracy of the numerical dispersion is calculated as a function of the frequency of the launched wave and time step of the numerical grid. It is shown that the numerical method does not reproduce the analytical results near the plasma resonances for any chosen value of time step if there is not a dissipation mechanism in the system. It means that FDTD method cannot be applied straightforward to simulate the problems where the plasma resonances play a key role (for example, the mode conversion problems). But the accuracy of the numerical scheme can be improved by introducing some artificial damping of the plasma currents. Although part of the wave power is lost in the system in this case but the numerical scheme describes the wave processes in an agreement with analytical predictions. Метод конечных разностей во временной области (КРВО) применяется для описания распространения поперечных электромагнитных волн через магнитоактивную плазму. Численное дисперсионное уравнение получено в приближении холодной плазмы. Точность численной дисперсии посчитана как функция частоты распространяющейся волны и величины временного шага численной сетки. Показано, что при отсутствии механизмов диссипации в системе численный метод не воспроизводит аналитические результаты возле плазменных резонансов для любого выбранного временного шага. Это значит, что метод КРВО нельзя применять прямолинейно для моделирования задач, в которых плазменные резонансы играют ключевую роль (например, в задачах по изучению конверсии мод). Но точность численной схемы можно улучшить через включение механизма затухания для плазменных токов. Хотя в этом случае часть энергии волны теряется в системе, но численная схема описывает волновые процессы в соответствии с аналитическими предсказаниями. Метод кінцевих різниць у часовій області (КРЧО) застосовується для вивчення поширення поперечних електромагнітних хвиль через магнітоактивну плазму. Числове дисперсійне рівняння отримано в наближенні холодної плазми. Точність числової дисперсії обрахована як функція частоти електромагнітної хвилі та величини часового кроку числової сітки. Показано, що за відсутністю механізмів дисипації в системі числовий метод не відтворює аналітичні результати біля плазмових резонансів для будь- якого вибраного часового кроку. Це означає, що метод КРЧО не можна застосовувати прямолінійно для моделювання задач, у яких плазмові резонанси відіграють ключову роль (наприклад,у задачах з вивчення конверсії мод). Але точність числової схеми можна покращити через включення механізму загасання плазмових струмів. Хоча в цьому випадку частина енергії хвилі втрачається в системі, але числова схема описує хвильові процеси у відповідності до аналітичних передбачень.